KLauS: an ASIC for silicon photomultiplier readout and its application in a setup for production testing of scintillating tiles - Briggl, Konrad; Dorn, Markus; Hagedorn, Rolf; Harion, Tobias; Schultz-Coulon, Hans-Christian; Shen, Wei (Journal of Instrumentation, 2014)
KLauS is an ASIC produced in the AMS 0.35 μm SiGe process to read out the charge signals from silicon photomultipliers. Developed as an analog front-end for future calorimeters with high granularity as pursued by the AHCAL concept in the CALICE collaboration, the ASIC is designed to measure the charge signal of the sensors in a large dynamic range and with low electronic noise contributions. In order to tune the operation voltage of each sensor individually, an 8-bit DAC to tune the voltage at the input terminal within a range of 2V is implemented. Using an integrated fast comparator with low jitter, the time information can be measured with sub-nanosecond resolution. The low power consumption of the ASIC can be further decreased using power gating techniques. Future versions of KLauS are under development and will incorporate an ADC with a resolution of up to 12-bits and blocks for digital data transmission. The chip is used in a setup for mass testing and characterization of scintillator tiles for the AHCAL test beam program.